2016
DOI: 10.1111/evo.13086
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of coexistence: Reciprocal adaptation promotes the assembly of a simple community

Abstract: Species coexistence may result by chance when co-occurring species do not strongly interact or it may be an evolutionary outcome of strongly interacting species adapting to each other. Although patterns like character displacement indicate that coexistence has often been an evolutionary outcome, it is unclear how often the evolution of coexistence represents adaptation in only one species or reciprocal adaptation among all interacting species. Here, we demonstrate a strong role for evolution in the coexistence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 66 publications
(183 reference statements)
1
40
0
Order By: Relevance
“…Additionally, the presence of guppies has been shown to reduce killifish growth rates while not affecting survival in a field reciprocal transplant experiment (Walsh et al. ) and in a mesocosm experiment (Bassar ). Thus, interactions between guppies and killifish are likely both predatory and competitive in nature and, as such, their relationship may best be described as intraguild predation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the presence of guppies has been shown to reduce killifish growth rates while not affecting survival in a field reciprocal transplant experiment (Walsh et al. ) and in a mesocosm experiment (Bassar ). Thus, interactions between guppies and killifish are likely both predatory and competitive in nature and, as such, their relationship may best be described as intraguild predation.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms causing killifish density to decline in the presence of guppies remains unknown; however, Fraser and Lamphere (2013) reported that guppies readily consume killifish eggs and neonates in the laboratory and that introduced guppies reduce killifish densities in a replicated field experiment. Additionally, the presence of guppies has been shown to reduce killifish growth rates while not affecting survival in a field reciprocal transplant experiment (Walsh et al 2011) and in a mesocosm experiment (Bassar 2017). Thus, interactions between guppies and killifish are likely both predatory and competitive in nature and, as such, their relationship may best be described as intraguild predation.…”
Section: Discussionmentioning
confidence: 99%
“…In response to changes in killifish presence, the guppies rapidly evolve differences in color, behavior, and life-history traits (see, e.g., Reznick and Endler 1982). Similarly, killifish lifehistory traits repeatedly diverge between natural ponds with and without guppies (Walsh and Reznick 2009).Using this model system, Bassar et al (2016) seek to address whether the observed changes in guppies and killifish promote * This manuscript corresponds to Bassar, R. D., Simon, T., Roberts, W., Travis, J., and Reznick, D. N. 2016. The evolution of coexistence: reciprocal adaptation promotes the assembly of a simple community.…”
mentioning
confidence: 99%
“…Using this model system, Bassar et al (2016) seek to address whether the observed changes in guppies and killifish promote * This manuscript corresponds to Bassar, R. D., Simon, T., Roberts, W., Travis, J., and Reznick, D. N. 2016. The evolution of coexistence: reciprocal adaptation promotes the assembly of a simple community.…”
mentioning
confidence: 99%
See 1 more Smart Citation